Classroom assessment concepts and applications - Russell, Michael K. 1967-; Airasian, Peter W. (McGraw-Hill, 2012)
"Assessment is a daily, ongoing, integral part of teaching and learning. Classroom Assessment: Concepts and Applications explores how assessment is a key component of all aspects of the instructional process, including organizing and creating a classroom culture, planning lessons, delivering instruction, and examining how students have grown as a result of instruction.